Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/hearts1010003
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Penetrating Aortic Ulcer

Abstract: Penetrating aortic ulceration (PAU) is part of the spectrum of acute aortic syndromes (AAS), and is defined as an ulcerated intimal disruption due to atherosclerotic disease. PAU may be simple, isolated and asymptomatic, or it may be symptomatic, aneurysmal and extensive; these may progress and lead to rupture. This review aims to evaluate the treatment options for PAU. Treatment options range from radiological surveillance, risk factor modification, best medical therapy and open or endovascular surgical repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
0
8
0
1
Order By: Relevance
“…2,[4][5][6][8][9]16,18,23,33,55 TEVAR is preferable in patients showing signs and symptoms of abdominal or limb ischemia, those with associated infectious aortitis especially mycotic and anatomical abnormality like coarctation. 18, 76 Cho et al suggested medical management for PAU and also expected resolution of IMH with time. 5 This approach was supported by other studies in regard to asymptomatic cases and those involving descending aorta.…”
Section: Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…2,[4][5][6][8][9]16,18,23,33,55 TEVAR is preferable in patients showing signs and symptoms of abdominal or limb ischemia, those with associated infectious aortitis especially mycotic and anatomical abnormality like coarctation. 18, 76 Cho et al suggested medical management for PAU and also expected resolution of IMH with time. 5 This approach was supported by other studies in regard to asymptomatic cases and those involving descending aorta.…”
Section: Managementmentioning
confidence: 99%
“…5 This approach was supported by other studies in regard to asymptomatic cases and those involving descending aorta. 12,17,36,46,76 When the IMH is seen in concurrence with PAU, urgent surgical management is an absolute indication in cases of Type A IMH. For Type B IMH the indications remain more or less the same as those for PAU.…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…This research is currently lacking, and larger studies or registries may be helpful in optimizing PAU management. [ 6 ] Future studies are required to have more definitive management protocols for such cases.…”
mentioning
confidence: 99%